2022
DOI: 10.9734/jpri/2022/v34i51a36444
|View full text |Cite
|
Sign up to set email alerts
|

Does Nifuroxazide Enhance the Effect of Metronidazole Oral Administration in the Treatment of Clostridium difficile Infection?

Abstract: Aims: To evaluate the efficacy of metronidazole monotherapy and modified therapy with metronidazole + nifuroxazidefor the for treatment of a mild form of Clostridium difficile infection (CDI). Study Design: A prospective, randomized, controlled clinical trial. Place and Duration of Study: University of Applied Sciences Tuzla in the period from June 2018 to June 2019. Methodology: Sixty patients were included in the study, divided into two groups. One group received standard therapy (metronida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Such medications include clarithromycin which is indicated for the treatment of H. pylori infection 4 and metronidazole which is used to enhance NFX antibacterial effect. 50 It was found that both tested medications have no effect on NSC-dots luminescence intensity and thus they did not interfere with NFX uorimetric analysis. Additionally, the good percentage recoveries presented in Table 3 demonstrate that the excipients and additives co-formulated within the pharmaceutical formulations did not affect the proposed luminescent methodology.…”
Section: Accuracy and Precisionmentioning
confidence: 96%
“…Such medications include clarithromycin which is indicated for the treatment of H. pylori infection 4 and metronidazole which is used to enhance NFX antibacterial effect. 50 It was found that both tested medications have no effect on NSC-dots luminescence intensity and thus they did not interfere with NFX uorimetric analysis. Additionally, the good percentage recoveries presented in Table 3 demonstrate that the excipients and additives co-formulated within the pharmaceutical formulations did not affect the proposed luminescent methodology.…”
Section: Accuracy and Precisionmentioning
confidence: 96%